Preparation method of pyrazole type metal Salen-based MOF (Metal Organic Framework) material

By preparing pyrazole-type metal Salen-based MOF materials in strong alkaline media, the problem of unstable such materials in the prior art in strong alkaline media is solved, and high stability and flexible catalytic effects are achieved, which is suitable for Photoelectric catalysis field.

CN119409985APending Publication Date: 2025-02-11JIAXING UNIV

Patent Information

Application Number
CN202411722412.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing metal-Salen-based MOFs are unstable in strongly alkaline or strong oxidative media, limiting their application in these media.

Method used

The corresponding M-pyrazolyl Salen ligand is chelated with cobalt salt, nickel salt, copper salt and iron salt to form the corresponding M-pyrazolyl Salen and mix it with Zn(OAc)2·2H2O in an organic solvent and water Hydrothermal reaction was carried out in the solution to prepare a highly stable pyrazole-type metal Salen-based MOF material.

Benefits of technology

High stability under strong alkaline conditions is achieved, and different catalytic effects can be achieved by flexibly changing the central metal of the ligand, and it is suitable for the field of photoelectrocatalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409985A_ABST
    Figure CN119409985A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a pyrazol type metal Salen-based MOF (Metal Organic Framework) material. The preparation method comprises the following steps: chelating a pyrazol functionalized Salen ligand with cobalt salt, nickel salt, copper salt and iron salt to generate corresponding M-pyrazol Salen; dispersing and dissolving the obtained M-pyrazolyl Salen and Zn (OAc) 2.2 H2O by using a mixed solution of an organic solvent and H2O; and carrying out hydrothermal reaction on the obtained mixed solution, washing and drying to obtain the M-SalenMOFs. The pyrazole type metal Salen-based MOF synthesized by the invention is novel and unique in structure, easy to regulate and control and high in stability, and has good stability under a strong alkaline condition; the obtained M-SalenMOFs can flexibly change the ligand center metal so as to realize different catalysis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal organic framework material synthesis, and specifically relates to a method for preparing a pyrazole-type metal-salen-based MOF material. Background Art

[0002] Metal Organic Frameworks (MOFs) or porous coordination polymers (PCPs) are composed of metal ions / clusters as "nodes" and organic ligands / linkers as "bridges". They are highly crystalline porous materials with periodic structural units. Compared with traditional porous materials, metal-organic framework materials have many advantages such as low density, large specific surface area, high porosity, regular structure, mild synthesis conditions, and novel and diverse framework structures.

[0003] Metal-Salen (N,N'-bis-(saliylaldehyde)ethylendiamine) complexes have been widely used in a variety of organic synthesis reactions in recent years due to their advantages such as convenient synthesis, high efficiency and low toxicity. However, their instability, easy self-polymerization and difficulty in separation from the reaction system in homogeneous catalysis have greatly limited their use. At present, a good strategy is to introduce metal-Salen into MOF or COF structures to achieve good heterogeneous catalytic effects. Some traditional metal linkers, such as porphyrin, phthalocyanine, 4, 4′-bipyridine, etc., can usually only chelate specific metals to assemble MOFs, while metal-Salen exhibits a wide range of central metal elements (to date, 74 different metal elements can be used to construct metal-Salen complexes), different coordination environments and different numbers of active metal centers, including single atomic sites, diatomic sites, and even trinuclear metal sites. These advantages have significantly promoted the use of metal-Salen as active sites to assemble MOF / COF materials for organic, gas adsorption and photoelectrocatalysis. For example, 202310479938.5 reported a Cr(III)-Salen-MOF catalyst prepared by the reaction of Cr(III)-Salen ligand and cadmium dichloride for catalyzing the copolymerization of SO2 and epoxides, but the catalytic central metal is relatively single. The literature (Adv. Mater. 2023, 35, 2304170) first reported the assembly of COF from M-Salen for photocatalytic CO2 reduction. Compared with other heterogeneous metal salt catalysts, MOF catalysts based on Salen metal salt-derived carboxylic acid linkers exhibited excellent catalytic performance, but the stability of these materials under aqueous reaction conditions was not satisfactory, while pyrazole MOFs exhibited good stability due to their own characteristics.

[0004] In summary, although great progress has been made in the synthesis of metal-salen-based MOFs, MOFs synthesized by metal-salen complexes are unstable in certain strong alkaline or strong oxidizing media, which limits their application in such media. By rationally designing the structure of metal-salen and immobilizing different low-valent transition metals, on the one hand, the stability of metal-salen catalysts can be improved and their recycling can be easily realized; on the other hand, MOFs immobilized with different types of metals can give full play to their catalytic advantages in the field of photoelectrocatalysis. Therefore, the development of a preparation method for highly stable pyrazole-type metal-salen-based MOF materials with cheap and readily available raw materials, simple operation, high efficiency and practicality has important scientific research and practical application value. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a pyrazole-type metal-Salen-based MOF material to solve the problems raised in the above background technology.

[0006] The object of the present invention is achieved through the following technical scheme: a method for preparing a pyrazole-type metal-Salen-based MOF material, specifically comprising the following steps:

[0007] Step 1, chelating 6,6'-((1E, 1'E)-((trans-1,2-cyclohexanediamine)bis(azacyclopentene))bis(methylcyclopentene)bis(2-(tert-butyl)-4-(1H-pyrazol-4-yl)phenol) with cobalt salt, nickel salt, copper salt, and iron salt to generate the corresponding M-pyrazolyl Salen;

[0008] Step 2, dissolving the M-pyrazolyl-Salen and Zn(OAc)2·2H2O obtained in step 1 by ultrasonic dispersion using a mixed solution of an organic solvent and H2O to obtain a mixed solution;

[0009] Step 3, subjecting the mixed solution obtained in step 2 to a hydrothermal reaction, washing, and drying to obtain a crystal precipitate.

[0010] Furthermore, the pyrazolyl-Salen ligand in step 1 is obtained by using 2-tert-butylphenol as the main raw material through bromination, formylation, Suzuki coupling, and ammonia aldehyde condensation, and the reaction process is as follows:

[0011]

[0012] Furthermore, the cobalt salt, nickel salt, copper salt and iron salt in step 1 are their corresponding nitrates, chlorates and acetates respectively;

[0013] The molar ratio of the pyrazolyl-salen to the cobalt salt, nickel salt, copper salt, and iron salt is 1:1.2, and the reaction solvent is methanol, ethanol, propanol, or butanol;

[0014] Ni(Cu)-pyrazolyl-Salen can be stirred overnight at room temperature, while Co(Fe)-pyrazolyl-Salen needs to be stirred overnight at 40℃~80℃ under nitrogen atmosphere. The reaction equation is as follows:

[0015]

[0016] Furthermore, in the step (2), the feed ratio of M-pyrazolyl-Salen to Zn(OAc)2·2H2O is 1:5 to 1:20.

[0017] Furthermore, the organic solvent in step 2 is DMF, DMSO or THF, and the volume ratio of the mixed solution of the organic solvent and H2O is 1:5 to 5:1.

[0018] Furthermore, in the hydrothermal reaction in step 3, the mixed solution obtained in step 2 is placed in a polytetrafluoroethylene reactor and reacted in an oven at 80 to 150° C. for 24 to 120 hours;

[0019] Among them, in step 3, DMF, deionized water and ethanol are used for washing in sequence, and the material is obtained by vacuum drying at 40-80°C for 12-16 hours, and the MOF material is obtained by centrifugal drying at 60°C for 12 hours, which is named M-Salen MOF.

[0020] The preparation method of pyrazole-type metal-Salen-based MOF material specifically comprises the following steps;

[0021] Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol, and then Ni(OAc)2·4H2O (0.248 g, 0.001 mol) was added and stirred at room temperature for 12 h. After the reaction, the mixture was filtered and washed with methanol and deionized water to obtain a light yellow powder.

[0022] Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol, heated to 60°C under N2 atmosphere, and then Co(OAc)2·4H2O (0.249 g, 0.001 mol) dissolved in 5 mL of anhydrous methanol was slowly added dropwise, and the mixture was stirred under reflux for 12 h. After the reaction, the mixture was filtered and washed with methanol and deionized water to obtain a dark red powder.

[0023] Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol, heated to 60°C under N2 atmosphere, and then slowly added dropwise with 5 mL of anhydrous methanol to dissolve Fe(OAc)2 (0.174 g, 0.001 mol), refluxed and stirred for 12 h, and after the reaction, filtered, washed with methanol and deionized water to obtain a black powder;

[0024] Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol and heated to 60°C under N2 atmosphere. Then, Cu(OAc)2 (0.182 g, 0.001 mol) dissolved in 5 mL of anhydrous methanol was slowly added dropwise. The mixture was refluxed and stirred for 12 h. After the reaction, the mixture was filtered and washed with methanol and deionized water to obtain a gray powder.

[0025] Application of pyrazole metal-Salen-based MOF materials in the field of photoelectrocatalysis.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention chelates the pyrazole-functionalized Salen ligand with cobalt salt, nickel salt, copper salt and iron salt to generate the corresponding M-pyrazolyl Salen; then the obtained M-pyrazolyl Salen and Zn(OAc)2·2H2O are dispersed and dissolved in a mixed solution of an organic solvent and H2O; the obtained mixed solution is subjected to a hydrothermal reaction, washed and dried to obtain M-Salen MOFs. The pyrazole-type metal-Salen-based MOF synthesized by the present invention has a novel and unique structure, is easy to control, has high stability, and has good stability under strong alkaline conditions; the obtained M-Salen MOFs can flexibly change the ligand center metal to achieve different catalytic properties. The pyrazole-type metal-Salen-based MOF synthesized by the present invention has a novel and unique structure, and the metal center is easy to control and has high stability.

[0028] In the preparation method provided by the present invention, the ligand central metal can be flexibly changed to achieve different catalysis. For example, the Ni-Salen MOF in the present invention can be used for electrocatalytic oxygen evolution reaction. -2 The cross point is 363mV. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a scanning electron microscope image of the Ni-Salen MOF prepared in Example 4;

[0030] Figure 2 Elemental mapping of Ni-Salen MOF prepared in Example 4;

[0031] Figure 3 This is a total element distribution diagram of the Ni-Salen MOF prepared in Example 4;

[0032] Figure 4 This is the X-ray electron spectrum of the Ni-Salen MOF prepared in Example 4;

[0033] Figure 5This is a diagram of nitrogen adsorption and desorption of Ni-Salen MOF prepared in Example 4;

[0034] Figure 6 This is the pore size distribution diagram of Ni-Salen MOF prepared in Example 4;

[0035] Figure 7 Thermogravimetric analysis diagram of Ni-Salen MOF prepared in Example 4;

[0036] Figure 8 X-ray diffraction pattern of Ni-Salen MOF prepared in Example 4;

[0037] Fig. 9 X-ray diffraction comparison diagram of Ni-Salen MOF prepared in Example 4 before and after soaking in 1M KOH, 0.1M HCI, and ACN for 7 days;

[0038] Fig.10 is the X-ray diffraction pattern of Fe-Salen MOF;

[0039] Fig.11 is the X-ray diffraction pattern of Co-Salen MOFX;

[0040] Fig.12 is the X-ray diffraction pattern of Cu-Salen MOF;

[0041] Fig.13 This is a scanning electron microscope image of Co-Salen MOF;

[0042] Fig.14 This is a scanning electron microscope image of Fe-Salen MOF.

[0043] Fig.15 Comparison chart of Ni-Salen MOF and commercial RuO2 LSV. DETAILED DESCRIPTION

[0044] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0045] Figure 1-15 As shown, a method for preparing a pyrazole-type metal-Salen-based MOF material specifically comprises the following steps:

[0046] Step 1, chelating 6,6'-((1E, 1'E)-((trans-1,2-cyclohexanediamine)bis(azacyclopentene))bis(methylcyclopentene)bis(2-(tert-butyl)-4-(1H-pyrazol-4-yl)phenol) with cobalt salt, nickel salt, copper salt, and iron salt to generate the corresponding M-pyrazolyl Salen;

[0047] Step 2, dissolving the M-pyrazolyl-Salen and Zn(OAc)2·2H2O obtained in step 1 by ultrasonic dispersion using a mixed solution of an organic solvent and H2O to obtain a mixed solution;

[0048] Step 3, subjecting the mixed solution obtained in step 2 to a hydrothermal reaction, washing, and drying to obtain a crystal precipitate.

[0049] In step 1, the pyrazolyl-Salen ligand is prepared from 2-tert-butylphenol as the main raw material through bromination, formylation, Suzuki coupling, and ammonia aldehyde condensation. The reaction process is as follows:

[0050]

[0051] The cobalt salt, nickel salt, copper salt and iron salt in step 1 are their corresponding nitrates, chlorates and acetates respectively;

[0052] The molar ratio of the pyrazolyl-salen to the cobalt salt, nickel salt, copper salt, and iron salt is 1:1.2, and the reaction solvent is methanol, ethanol, propanol, or butanol;

[0053] Ni(Cu)-pyrazolyl-Salen can be stirred overnight at room temperature, while Co(Fe)-pyrazolyl-Salen needs to be stirred overnight at 40℃~80℃ under nitrogen atmosphere. The reaction equation is as follows:

[0054]

[0055] In the step 2, the feed ratio of M-pyrazolyl-Salen to Zn(OAc)2·2H2O is 1:5 to 1:20.

[0056] The organic solvent in step 2 is DMF, DMSO or THF, and the volume ratio of the mixed solution of the organic solvent and H2O is 1:5 to 5:1.

[0057] In the hydrothermal reaction in step 3, the mixed solution obtained in step 2 is placed in a polytetrafluoroethylene reactor and reacted in an oven at 80 to 150° C. for 24 to 120 hours;

[0058] Among them, in step 3, DMF, deionized water and ethanol are used for washing in sequence, and the material is obtained by vacuum drying at 40-80°C for 12-16 hours, and the MOF material is obtained by centrifugal drying at 60°C for 12 hours, which is named M-Salen MOF. Specific embodiment 1:

[0060] The method for synthesizing the pyrazole-functionalized Salen ligand of this embodiment comprises the following steps:

[0061] (1) The crude product obtained in the previous step was dissolved in 87 mL of acetonitrile, and then paraformaldehyde (11.13 g, 0.39 mol) and anhydrous magnesium chloride (13.30 g, 0.11 mol) were added in sequence. During the stirring process, 28 mL of triethylamine was slowly added dropwise, and the mixture was heated under reflux at 75°C for 4 h. After the reaction was completed, the reaction mixture was poured into ice water to quench the reaction, filtered, and the filter cake was dissolved in ethyl acetate and washed with 1 M HCl. The solution changed from wine red to yellow. The organic phases were combined, washed with salt 2 to 3 times, and the solvent was removed by distillation under reduced pressure to obtain a crude product of light yellow oil.

[0062] (2) 4-pyrazoleboronic acid pinacol ester (10.00 g, 0.052 mol) was weighed in a round-bottom flask, and 150 mL of dichloromethane was added to dissolve it, followed by the addition of di-tert-butyl dicarbonate (15 mL, 0.062 mol). After complete dissolution, 10 mL of triethylamine was slowly added dropwise, and the mixture was stirred at room temperature for 36 h. After the reaction was completed, water was added to quench the reaction, and the organic phase was separated by standing. The aqueous phase was extracted with dichloromethane three times, the organic phases were combined, and the salt was washed 2 to 3 times. The solvent was removed by distillation under reduced pressure to obtain a white powder product.

[0063] (3) 2-Hydroxy-3-tert-butyl-5-bromo-benzoic acid (4.00 g, 0.016 mol), 4-pyrazoleboronic acid pinacol ester (4.7 g, 0.016 mol), tetrakis(triphenylphosphine palladium) (300 mg, 0.00026 mol) and anhydrous potassium carbonate (10.00 g, 0.072 mol) were weighed in a round-bottom flask, and a mixed solution of 80 mL of 1-4-dioxane and 20 mL of deionized water was added to dissolve the mixture. The mixture was reacted at 110° C. for 36 h under nitrogen protection. After the reaction was completed, the solvent was evaporated under reduced pressure, the mixture was dissolved in ethyl acetate, washed with water and salt, and the organic phases were combined, spin-dried and separated by column chromatography (petroleum ether:ethyl acetate=1:1) to obtain a light yellow product. 1 H NMR (400MHz, Chloroform-d) δ 11.76 (s, 1H), 9.90 (s, 1H), 7.84 (s, 2H), 7.64 (d, J = 2.0Hz, 1H), 7.49 (d, J = 2.1Hz, 1H), 1.45 (s, 9H). 13 C NMR (101MH z, Chloroform-d) δ197.16,159.94,138.85,132.20,132.06,128.72,128.54,123.91,121.66,120.67,34.91,29.17.

[0065] (4) 2-Hydroxy-3-tert-butyl-5-(1-H-4-pyrazole)benzaldehyde (5.10 g, 0.02 mol) was weighed into a three-necked flask, and 40 mL of anhydrous methanol was added. The mixture was stirred and dissolved under N2 protection, and heated to 60°C. Then, trans-1,2-cyclohexanediamine (1.19 g, 0.01 mol) was weighed and dissolved in 5 mL of anhydrous methanol. The mixture was slowly added dropwise to the reaction solution in five portions for a total of 10 min. The mixture was reacted for 12 h, and a yellow product was obtained by column chromatography (petroleum ether: ethyl acetate = 1:2). 1 H NMR (400MHz, Chloroform-d) δ13.92(s,2H),8.23(s,2H),7.64(s,4H),7.32(s,2H),7.02(s,2H),3.35-3.24(m,2H),2.11-1.47(m,8H),1.40(s,18H). 13 C NMR (101MHz, Chloroform-d) δ165.60,159.22,137.60,127.33,126.78,122.42,122.21,118.57,72.16,34.79,32.91,29.31,24.25. Specific embodiment 2:

[0067] The synthetic method steps of M-pyrazolyl-Salen of the present embodiment are as follows:

[0068] (1) Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol, and then Ni(OAc)2·4H2O (0.248 g, 0.001 mol) was added and stirred at room temperature for 12 h. After the reaction, the mixture was filtered and washed with methanol and deionized water to obtain a light yellow powder.

[0069] (2) Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol and heated to 60°C under a N2 atmosphere. Then, Co(OAc)2·4H2O (0.249 g, 0.001 mol) dissolved in 5 mL of anhydrous methanol was slowly added dropwise. The mixture was refluxed and stirred for 12 h. After the reaction, the mixture was filtered and washed with methanol and deionized water to obtain a dark red powder.

[0070] (3) Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol and heated to 60°C under a N2 atmosphere. Then, Fe(OAc)2 (0.174 g, 0.001 mol) dissolved in 5 mL of anhydrous methanol was slowly added dropwise. The mixture was refluxed and stirred for 12 h. After the reaction, the mixture was filtered and washed with methanol and deionized water to obtain a black powder.

[0071] (4) Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol and heated to 60°C under a N2 atmosphere. Then, Cu(OAc)2 (0.182 g, 0.001 mol) dissolved in 5 mL of anhydrous methanol was slowly added dropwise. The mixture was refluxed and stirred for 12 h. After the reaction, the mixture was filtered and washed with methanol and deionized water to obtain a gray powder.

[0072] The synthesis conditions of MOF materials with different metal centers are roughly the same. The main synthesis conditions screening include: the ratio of ligand to metal salt, the volume ratio of mixed solvent, reaction time and temperature. The following takes the exploration of synthesis conditions of Ni-Salen MOF as an example to illustrate. Specific embodiment 3:

[0074] A method for preparing a pyrazole-type Ni-Salen-based MOF material is achieved by the following steps:

[0075] Weigh Ni-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (15 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 4.2 mL N, N-dimethylformamide and 2.8 mL deionized water. Ultrasonic dispersion is performed for 30 min. After sealing, the mixture is placed in an oven at 120°C for 72 h. After cooling to room temperature, the upper layer of clear water is removed, and the lower layer of crystal precipitate is taken out. The mixture is washed with N, N-dimethylformamide, deionized water and methanol, and then dried under vacuum at 80°C for 12 h. Block-shaped bimetallic Ni-Salen MOF materials are obtained. Specific embodiment 4:

[0077] A method for preparing a pyrazole-type Ni-Salen-based MOF material is achieved by the following steps:

[0078] Weigh Ni-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (30 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 4.2 mL N, N-dimethylformamide and 2.8 mL deionized water. Ultrasonic dispersion is performed for 30 min. After sealing, the mixture is placed in an oven at 120 ° C for 72 h. After cooling to room temperature, the upper layer of clear water is sucked off, and the lower layer of crystal precipitation is taken out. The mixture is washed with N, N-dimethylformamide, deionized water and methanol, and then placed under vacuum drying at 80 ° C for 12 h. Block bimetallic Ni-Salen MOF material is obtained. Under this condition, the yield of the crystal material is the highest, the particle size is the most uniform, and the yield is the highest.

[0079] The single crystal diffraction data of the product obtained in Example 4 were obtained by Rigaku R-AXIS SPIDER X-ray diffractometer using a copper target (wavelength ) scanning. The diffraction data were absorption corrected by the Crystal Clear program. The single crystal structure was reduced, structurally analyzed and refined by the SHELXTL-2016 program package. The Ni ions in the asymmetric unit were first anisotropically refined, while the other atoms (C, O, N) in the salen ligand were only isotropically refined due to their weaker electronic intensity. The DELU, SIMU and DFIX restraint commands were used in the refinement process. The highly disordered residual guest molecules in the structure were removed by the SQUEEE subcommand in the PLATON software.

[0080] Table 1

[0081]

[0082]

[0083] Table 1 shows the crystallographic data of the product obtained in specific Example 2. The specific crystallographic data of the product obtained in Example 3 can be seen from the table.

[0084] The crystal morphology and size obtained in specific embodiment 4 are as follows Figure 1 As shown, the size is 50-60 micron cuboid. The surface composition of Ni-Salen MOF was detected by X-ray photoelectron spectroscopy (XPS). The full spectrum scan of Ni-Salen MOF is shown in Figure 4 As shown, Ni, Zn, N, O, and C are present, which is consistent with the EDS mapping results ( Figure 2 , 3 ). Powder X-ray diffraction pattern of Ni-Salen MOF sample ( Figure 8 ) is in good agreement with the single crystal structure simulation results, confirming the phase purity of the sample. i-SalenMOF Nitrogen adsorption desorption diagram ( Figure 5) can be seen that the line shape of the adsorption isotherm curve shows reversible type I gas adsorption and desorption behavior. The specific surface area of ​​Ni-Salen MOF is 629m 2 g -1 , indicating that it has a rich microporous structure, the pore size distribution diagram ( Figure 6 ) also confirmed this point. The results of thermogravimetric analysis show that Ni-Salen MOF can maintain high structural stability within 430℃. Specific embodiment 5:

[0086] A method for preparing a pyrazole-type Ni-Salen-based MOF material is achieved by the following steps:

[0087] Weigh Ni-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (60 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 4.2 mL N, N-dimethylformamide and 2.8 mL deionized water. Ultrasonic dispersion was performed for 30 min. After sealing, the mixture was placed in an oven at 120°C for 72 h. After cooling to room temperature, the upper layer of clear water was removed, and the lower layer of crystal precipitate was taken out. The mixture was washed with N, N-dimethylformamide, deionized water and methanol, and then dried under vacuum at 80°C for 12 h. Block-shaped bimetallic Ni-Salen MOF materials were obtained. Specific embodiment 6:

[0089] Appropriate amounts of Ni-Salen MOF were weighed and immersed in 1M KOH, 0.1M HCI, and ACN for seven days, respectively. The mixture was washed clean and dried in a vacuum oven. XRD tests were performed to evaluate the stability of Ni-Salen MOF.

[0090] The XRD test results obtained in this example are as follows Figure 9 As shown, after Ni-Salen MOF was soaked for seven days, it was found that the three materials could maintain a stable crystalline form in strong alkalinity and common organic solvents. In a pH = 2 HCl aqueous solution, the diffraction intensity of the small-angle diffraction peak weakened and the stability decreased, but in general, Ni-Salen MOF can be maintained in common organic solvents and strong alkaline solvents.

[0091] Weigh Ni-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (60 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 4.2 mL N, N-dimethylformamide and 2.8 mL deionized water. Ultrasonic dispersion was performed for 30 min. After sealing, the mixture was placed in an oven at 120°C for 72 h. After cooling to room temperature, the upper layer of clear water was removed, and the lower layer of crystal precipitate was taken out. The mixture was washed with N, N-dimethylformamide, deionized water and methanol, and then dried under vacuum at 80°C for 12 h. Block-shaped bimetallic Ni-Salen MOF materials were obtained.

[0092] Comparative Example 1:

[0093] A method for preparing a pyrazole-type Ni-Salen-based MOF material is achieved by the following steps:

[0094] Weigh Ni-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (30 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 1.2 mL N, N-dimethylformamide and 4.8 mL deionized water. Ultrasonic dispersion was performed for 30 min. After sealing, the mixture was placed in an oven at 120°C for 72 h. After cooling to room temperature, the upper layer of clear water was removed, and the lower layer of crystal precipitate was taken out. The mixture was washed with N, N-dimethylformamide, deionized water and methanol, and then dried under vacuum at 80°C for 12 h. A small amount of blocky bimetallic Ni-Salen MOF material was obtained.

[0095] Comparative Example 2

[0096] A method for preparing a pyrazole-type Ni-Salen-based MOF material is achieved by the following steps:

[0097] Ni-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (30 mg) were weighed and dissolved in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 4.8 mL N, N-dimethylformamide and 1.2 mL deionized water. Ultrasonic dispersion was performed for 30 min. After sealing, the mixture was placed in an oven at 120°C for 72 h. After cooling to room temperature, the upper layer of clear water was aspirated, and the lower layer of crystal precipitate was taken out. The mixture was washed with N, N-dimethylformamide, deionized water and methanol, and then dried under vacuum at 80°C for 12 h. The yield of the obtained blocky bimetallic Ni-Salen MOF material was not high.

[0098] Comparative Example 3

[0099] A method for preparing a pyrazole-type Ni-Salen-based MOF material is achieved by the following steps:

[0100] Weigh Ni-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (30 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 4.2 mL N, N-dimethylformamide and 2.8 mL deionized water. Perform ultrasonic dispersion for 30 min, seal the reactor, and place the reactor in an oven at 80°C for 72 h. After cooling to room temperature, remove the upper layer of clear water, take out the lower layer of crystal precipitate, wash it with N, N-dimethylformamide, deionized water, and methanol, and then place it in a vacuum oven at 80°C for 12 h. An amorphous flocculent product was obtained.

[0101] Comparative Example 4

[0102] A method for preparing a pyrazole-type Ni-Salen-based MOF material is achieved by the following steps:

[0103] Weigh Ni-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (30 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 4.2 mL N, N-dimethylformamide and 2.8 mL deionized water. Perform ultrasonic dispersion for 30 min, seal the reactor, and place the reactor in an oven at 150°C for 72 h. After cooling to room temperature, remove the upper layer of clear water, take out the lower layer of crystal precipitate, wash it with N, N-dimethylformamide, deionized water, and methanol, and then place it in a vacuum oven at 80°C for 12 h. An amorphous flocculent product was obtained.

[0104] Comparative Example 5

[0105] A method for preparing a pyrazole-type Ni-Salen-based MOF material is achieved by the following steps:

[0106] Weigh Ni-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (30 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 4.2 mL N, N-dimethylformamide and 2.8 mL deionized water. Ultrasonic dispersion is performed for 30 min. After sealing, the mixture is placed in an oven at 120°C for 24 h. After cooling to room temperature, the upper layer of clear water is removed, and the lower layer of crystal precipitation is taken out. The mixture is washed with N, N-dimethylformamide, deionized water and methanol, and then placed in a vacuum dryer at 80°C for 12 h. A small amount of bimetallic Ni-Salen MOF material is obtained.

[0107] Comparative Example 6

[0108] A method for preparing a pyrazole-type Ni-Salen-based MOF material is achieved by the following steps:

[0109] Weigh Ni-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (30 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 4.2 mL N, N-dimethylformamide and 2.8 mL deionized water. Perform ultrasonic dispersion for 30 min, seal the mixture, and place it in an oven at 120 °C for 120 h. After cooling to room temperature, remove the upper layer of clear water, take out the lower layer of crystal precipitate, wash it with N, N-dimethylformamide, deionized water and methanol, and then place it under vacuum drying at 80 °C for 12 h. Obtain a block of bimetallic Ni-Salen MOF material.

[0110] Comparative Example 7

[0111] A method for preparing a pyrazole-type Co-Salen-based MOF material is achieved by the following steps:

[0112] Co-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (30 mg) were weighed and dissolved in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 3.5 mL N, N-dimethylformamide and 3.5 mL deionized water. Ultrasonic dispersion was performed for 30 min. After sealing, the mixture was placed in an oven at 120°C for 72 h. After cooling to room temperature, the upper layer of clear water was aspirated, and the lower layer of crystal precipitate was taken out. The mixture was washed with N, N-dimethylformamide, deionized water and methanol successively, and then dried under vacuum at 80°C for 12 h. Block-shaped bimetallic Co-Salen MOF materials were obtained.

[0113] The scanning electron microscope image of Co-Salen MOF obtained in this comparative example ( Fig.12 ) It can be seen that the crystals are blocky and of different sizes. From the X-ray diffraction pattern ( Fig.10 ) can also be seen that the main peaks of the experimental data and the simulated data correspond well, but due to the problem of crystallinity, some characteristic peaks overlap into a broad peak, but its structure can be basically determined.

[0114] Comparative Example 8

[0115] A method for preparing a pyrazole Fe-Salen-based MOF material is achieved by the following steps:

[0116] Weigh Fe-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (30 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 3.5 mL N, N-dimethylformamide and 3.5 mL deionized water. Ultrasonic dispersion is performed for 30 min. After sealing, the mixture is placed in an oven at 120°C for 72 h. After cooling to room temperature, the upper layer of clear water is removed, and the lower layer of crystal precipitate is taken out. The mixture is washed with N, N-dimethylformamide, deionized water and methanol, and then dried under vacuum at 80°C for 12 h. Block-shaped bimetallic Fe-Salen MOF materials are obtained.

[0117] The Fe-Salen MOF scanning electron microscopy image obtained in this comparative example ( Fig.13 ) It can be seen that the crystal is blocky with a rough surface. From the X-ray diffraction pattern ( Fig. 9 ) It can also be seen that the main peaks of the experimental data and the simulated data correspond well, and its structure can be basically determined.

[0118] Comparative Example 9

[0119] A method for preparing a pyrazole-type Cu-Salen-based MOF material is achieved by the following steps:

[0120] Weigh Cu-pyrazolyl-Salen (15 mg) and Zn(OAc)2·2H2O (30 mg) and dissolve them in a 10 mL polytetrafluoroethylene reactor containing a mixed solution of 3.5 mL N, N-dimethylformamide and 3.5 mL deionized water. Perform ultrasonic dispersion for 30 min, seal the mixture, and place it in an oven at 110 °C for 72 h. After cooling to room temperature, remove the upper layer of clear water, take out the lower layer of crystal precipitate, wash it with N, N-dimethylformamide, deionized water and methanol, and then place it under vacuum drying at 80 °C for 12 h. Obtain a bulk bimetallic Cu-Salen MOF material.

[0121] From the X-ray diffraction pattern of Cu-Salen MOF ( Fig.11 ) It can be seen that there is a certain degree of deviation between the main peaks of the experimental data and the simulated data, which is considered to be the influence of the ligand center example on the crystal structure.

[0122] The Ni-Salen MOF obtained in Example 4 was activated in a vacuum oven at 120°C for 12h, and the Ni-Salen MOF was made into an electrode for oxygen evolution reaction (OER) activity test and compared with the commercial RuO2 catalyst. The results are shown in Fig.14 .

[0123] Fig.14The test results show that the Ni-Salen MOF prepared in the present invention has a good catalytic effect as an electrocatalytic oxygen evolution reaction (OER). -2 The potential at 363 mV is equivalent to 337 mV of commercial RuO2. When the voltage is greater than 1.63 V, the current density of Ni-Salen MOF is greater than that of commercial RuO2. The above results fully illustrate that the Ni-Salen MOF prepared by the present invention has a good prospect for electrocatalytic application.

[0124] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

[0125] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a pyrazole-type metal-Salen-based MOF material, characterized in that: The specific steps include: Step 1, chelating 6,6'-((1E, 1'E)-((trans-1,2-cyclohexanediamine)bis(azacyclopentene))bis(methylcyclopentene)bis(2-(tert-butyl)-4-(1H-pyrazol-4-yl)phenol) with cobalt salt, nickel salt, copper salt, and iron salt to generate the corresponding M-pyrazolyl Salen; Step 2, dissolving the M-pyrazolyl-Salen and Zn(OAc)2·2H2O obtained in step 1 by ultrasonic dispersion using a mixed solution of an organic solvent and H2O to obtain a mixed solution; Step 3, subjecting the mixed solution obtained in step 2 to a hydrothermal reaction, washing, and drying to obtain a crystal precipitate.

2. The method for preparing the pyrazole-type metal-Salen-based MOF material according to claim 1, characterized in that: In step 1, the pyrazolyl-Salen ligand is prepared from 2-tert-butylphenol as the main raw material through bromination, formylation, Suzuki coupling, and ammonia aldehyde condensation. The reaction process is as follows:

3. The method for preparing the pyrazole-type metal-Salen-based MOF material according to claim 2, characterized in that: The cobalt salt, nickel salt, copper salt and iron salt in step 1 are their corresponding nitrates, chlorates and acetates respectively; The molar ratio of the pyrazolyl-salen to the cobalt salt, nickel salt, copper salt, and iron salt is 1:1.2, and the reaction solvent is methanol, ethanol, propanol, or butanol; Ni(Cu)-pyrazolyl-Salen can be stirred overnight at room temperature, while Co(Fe)-pyrazolyl-Salen needs to be stirred overnight at 40℃~80℃ under nitrogen atmosphere. The reaction equation is as follows:

4. The method for preparing the pyrazole-type metal-Salen-based MOF material according to claim 3, characterized in that: In the step 2, the feed ratio of M-pyrazolyl-Salen to Zn(OAc)2·2H2O is 1:5 to 1:

20.

5. The method for preparing the pyrazole-type metal-Salen-based MOF material according to claim 4, characterized in that: The organic solvent in step 2 is DMF, DMSO or THF, and the volume ratio of the mixed solution of the organic solvent and H2O is 1:5 to 5:

1.

6. The method for preparing the pyrazole-type metal-Salen-based MOF material according to claim 5, characterized in that: In the hydrothermal reaction in step 3, the mixed solution obtained in step 2 is placed in a polytetrafluoroethylene reactor and reacted in an oven at 80 to 150° C. for 24 to 120 hours; Among them, in step 3, DMF, deionized water and ethanol are used for washing in sequence, and the material is obtained by vacuum drying at 40-80°C for 12-16 hours, and the MOF material is obtained by centrifugal drying at 60°C for 12 hours, which is named M-Salen MOF.

7. The method for preparing the pyrazole-type metal-Salen-based MOF material according to claim 1, characterized in that: The specific steps include: Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol, and then Ni(OAc)2·4H2O (0.248 g, 0.001 mol) was added and stirred at room temperature for 12 h. After the reaction, the mixture was filtered and washed with methanol and deionized water to obtain a light yellow powder. Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol, heated to 60°C under N2 atmosphere, and then Co(OAc)2·4H2O (0.249 g, 0.001 mol) dissolved in 5 mL of anhydrous methanol was slowly added dropwise, and the mixture was stirred under reflux for 12 h. After the reaction, the mixture was filtered and washed with methanol and deionized water to obtain a dark red powder. Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol, heated to 60°C under N2 atmosphere, and then slowly added dropwise with 5 mL of anhydrous methanol to dissolve Fe(OAc)2 (0.174 g, 0.001 mol), refluxed and stirred for 12 h, and after the reaction, filtered, washed with methanol and deionized water to obtain a black powder; Pyrazolyl-Salen (0.566 g, 0.001 mol) was dissolved in 100 mL of anhydrous methanol and heated to 60°C under N2 atmosphere. Then, Cu(OAc)2 (0.182 g, 0.001 mol) dissolved in 5 mL of anhydrous methanol was slowly added dropwise. The mixture was refluxed and stirred for 12 h. After the reaction, the mixture was filtered and washed with methanol and deionized water to obtain a gray powder.

8. Application of the pyrazole metal-salen-based MOF material according to any one of claims 1 to 7 in the field of photoelectrocatalysis.

Citation Information

Patent Citations

  • Cr (III)-Salen-MOF heterogeneous catalyst and application thereof

    CN116655931A

Cited By

  • A bimetallic organic framework multifunctional enzyme and its preparation method and application

    CN119771505A